Dampak Ajaran Alkitab Tentang Allah Terhadap Perilaku Peduli Lingkungan Mahasiswa - Andre Jonathan Tambunan; Intan Sari Panggabean; Meliana Rointan Silaban; Meisan Jaya Haro; Samelino Aritonang; Rapael Purba (Studia : Journal of Humanities and Education Studies, 2026)
The current global environmental crisis demands a response that is not only ecological but also theological in nature. For Christians, the biblical teachings about God as Creator and Sustainer of the universe should serve as the foundation for shaping environmentally responsible behavior. This study aims to analyze the impact of students' understanding of biblical teachings about God on their environmental care behavior at the Electrical Engineering Education Study Program, Universitas Negeri Medan. This study employed a descriptive qualitative method with data collected through observation, semi-structured interviews, a questionnaire consisting of 15 statement items, and documentation. The research subjects were 5 students selected purposively. Data were analyzed using an interactive model comprising data reduction, data presentation, and conclusion drawing. The results indicate that all respondents demonstrated good theological understanding, with 100% stating they understand God as Creator, believe humans are responsible for caring for the environment, and feel that biblical teachings influence their environmental behavior. In terms of behavioral aspects, most respondents showed positive actions such as disposing of waste properly and maintaining campus cleanliness; however, consistency in reducing plastic use and conserving energy still needs improvement. This study implies the importance of strengthening applicative eco-theology education on campus to transform theological knowledge into consistent and sustainable character habituation.